PROFIL PROTEIN BERBASIS SDS-PAGE ULAT SAGU (RHYNCHOPHORUS FERRUGINESUS) HASIL PEMANGGANGAN DENGAN OVEN DAN MICROWAVE - Sri Elvira; Ana Hidayati Mukaromah; Stalis Norma Ethica (Universitas Muhammadiyah Semarang, 2018)
Sago larvae (Rhynchophorus ferruginesus) is a source of animal protein originated from Papua, which has a high protein content. One of the disadvantages of sago larvae as a food ingredient is that it decomposes easily. To avoid decay, preservation could be done by heating with an oven and microwave, but the influence of the heating process to the quality of protein needs to be investigated. The purpose of this study was to analyze the profile of sago larvae protein baked in an oven and microwave with a time variation of sago larvae. The method used was SDS-PAGE (Sodium Dodecyl Sulfate– Polyacrylamide Gel Electrophoresis). The samples used were 13 sago larvae. Alarvae sample was used as a control and was not roasted with an oven and microwave, 6 larvae were baked with an oven with a variation of time 1, 2 and 3 minutes then the other 6 were roasted by microwave with a time variation of 1, 2 and 3 minutes. The results showed that sago larvae as a control had a number of protein bands 26, unlike the protein bands after baking with an oven and microwave. Larvae that have been baked in the oven for 1 minute found 17 protein bands, 20 protein bands were found for 2 minutes, and for 3 minutes were found 10 protein bands. Whereas in the sago larvae sample which was baked in the microwave for 1 minute found 16 protein bands, for 2 minutes found 11 protein bands and for 3 minutes found 12 protein bands. These results indicatedthe longer the heating time, the higher the level of protein denaturation.This marked by more protein bands on protein profile with smaller molecular weight values.Keywords: roasting, sago larvae, SDS-PAGE